2022
DOI: 10.3389/fped.2022.1010016
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring disease progression in childhood bronchiectasis

Abstract: Bronchiectasis (not related to cystic fibrosis) is a chronic lung disease caused by a range of etiologies but characterized by abnormal airway dilatation, recurrent respiratory symptoms, impaired quality of life and reduced life expectancy. Patients typically experience episodes of chronic wet cough and recurrent pulmonary exacerbations requiring hospitalization. Early diagnosis and management of childhood bronchiectasis are essential to prevent respiratory decline, optimize quality of life, minimize pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 72 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…In addition, there is a need and recent interest for noninvasive biomarkers to investigate bronchiectasis. 15,24,32 To date, the existing literature related to this finding appears inconsistent. In this study, we found that bronchiectasis reversibility was not rare, occurring in a substantial proportion of the study population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, there is a need and recent interest for noninvasive biomarkers to investigate bronchiectasis. 15,24,32 To date, the existing literature related to this finding appears inconsistent. In this study, we found that bronchiectasis reversibility was not rare, occurring in a substantial proportion of the study population.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is a need and recent interest for non‐invasive biomarkers to investigate bronchiectasis 15,24,32 . To date, the existing literature related to this finding appears inconsistent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations